Creative Sparks: Works of Nature, Selection, and the Human Author - Burstyn, Neal F. (The Columbia Journal of Law & the Arts, 2016)
It is now common knowledge that if you put a bunch of monkeys in a room with a typewriter, they will eventually reproduce the works of Shakespeare. But according to the United States Copyright Office, if you give that same group of monkeys a camera, you do not get copyright in any pictures they may happen to take. In 2011, British wildlife photographer David Slater was in Indonesia when a group of crested black macaques began playing with his camera equipment and snapped some pictures, one of which went viral and proved temporarily profitable for Slater. The image became the source of dispute when Wikipedia refused Slater’s request to remove the image from its website and asserted that the photograph was taken by an animal and was therefore uncopyrightable.5 Seemingly in response to this squabble, the Copyright Office updated the section on the “human authorship” requirement in the Third Edition of its Compendium, stating that it “will not register works produced by nature, animals, or plants” and cites, inter alia, “[a] photograph taken by a monkey” as an example.6 Referring to Burrow-Giles Lithographic Co. v. Sarony, the Compendium asserts that “[t]o qualify as a work of ‘authorship’ a work must be created by a human being” and “[w]orks that do not satisfy this requirement are not copyrightable.” Given the Copyright Office’s explicit rejection of any cognizable copyright protection in photographs taken by a monkey, any legal action taken by Slater is likely to fail. Although Slater’s situation appears to be an open and shut case when viewed in isolation, the occurrence triggers larger issues, especially where artists may be prevented from capitalizing on works that are capable of producing substantial income. This Note seeks to break down and understand the Copyright Office and circuit courts’ aversion to recognizing a protectable copyright interest in works “authored” by nature and explore any inconsistencies. It seems clear that something in the copyright system is out of sync with reality when countless works of little to no cultural significance can claim copyright protection, while other works that exhibit far more intellectual, physical, or monetary investment will be left defenseless. The monkey selfie debacle and other examples will be used as specimens for understanding the issues at play, as other cases and theories are investigated